2019
DOI: 10.1017/jfm.2019.222
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between super-hydrophobic, liquid infused and rough surfaces: a direct numerical simulation study

Abstract: Direct Numerical Simulations of two superposed fluids in a channel with a textured surface on the lower wall have been carried out. A parametric study varying the viscosity ratio between the two fluids has been performed to mimic both idealised superhydrophobic and liquid-infused surfaces and assess its effect on the frictional, form and total drag for three different textured geometries: longitudinal square bars, transversal square bars and staggered cubes. The interface between the two fluids is assumed to b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 46 publications
8
43
0
Order By: Relevance
“…The incompressible two-dimensional creeping flow equations for the generic unknown (u, p) are solved with a finite element method using the FreeFEM open source code [29]. The approach is based on a weak formulation of the equations, which means This provides an indication also of the geometries to be preferentially tested in cases where the microcavities are filled with an immiscible lubricant fluid (such as air or vapor, when considering superhydrophobic coatings); first order results [28] confirm this indication and feature-resolving direct numerical simulations of turbulence in a channel bound by lubricantimpregnated walls [30] further highlight the significance of wall-normal velocity fluctuations and their strong correlation to the total drag. The high-order approach described here can easily be extended to the case of lubricant-filled micro-cavities, to better capture phenomena which, to date, have only been modelled using the (first-order) Navier condition.…”
Section: Appendix 1: Numerical Approachmentioning
confidence: 87%
“…The incompressible two-dimensional creeping flow equations for the generic unknown (u, p) are solved with a finite element method using the FreeFEM open source code [29]. The approach is based on a weak formulation of the equations, which means This provides an indication also of the geometries to be preferentially tested in cases where the microcavities are filled with an immiscible lubricant fluid (such as air or vapor, when considering superhydrophobic coatings); first order results [28] confirm this indication and feature-resolving direct numerical simulations of turbulence in a channel bound by lubricantimpregnated walls [30] further highlight the significance of wall-normal velocity fluctuations and their strong correlation to the total drag. The high-order approach described here can easily be extended to the case of lubricant-filled micro-cavities, to better capture phenomena which, to date, have only been modelled using the (first-order) Navier condition.…”
Section: Appendix 1: Numerical Approachmentioning
confidence: 87%
“…The flat air-liquid interface approximation used to model superhydrophobic surfaces sustaining laminar-turbulent transitional flows has been a posteriori justified by Seo & Mani (2018), who reported no appreciable flow modification in considering the free-surface dynamics while measuring drag reduction compatible with the ones measured by Gose et al (2018). Thus, considering 'vanishingly small' textures (Fairhall, Abderrahaman-Elena & García-Mayoral 2018) for which the gas-liquid surface dynamics is negligible with respect to other factors (Arenas et al 2019), it is generally agreed that the surface can be modelled by a flat wall characterised by alternating no-slip and shear-free zones, as discussed, to cite a few, by Ybert et al (2007), Martell, Perot & Rothstein (2009), Jelly, Jung & Zaki (2014) and Rastegari & Akhavan (2015). Even though such approximations allow for the use of the single phase, incompressible Navier-Stokes equations, accurate simulations remain computationally demanding (Seo & Mani 2016).…”
Section: State Of the Artmentioning
confidence: 99%
“…The plastron loss is accelerated by the high shear of turbulent flows and further exacerbated by the hydrostatic pressure as well as many environmental variables [7] inevitable in open-water tests. For turbulent flows, while numerical studies have shown definite drag reduction and brought insights into the drag-reducing mechanism [9][10][11][12], experimental studies have reported mixed results, varying from substantial to negligible drag reduction, and even drag increase. Figure 1 summarizes the recent experimental studies of SHPo drag reduction in turbulent flows [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%